Gut microbiota modulates bleomycin-induced acute lung injury response in mice - Yoon, Young me; Hrusch, Cara L.; Fei, Na; Barrón, Gabriel M.; Mills, Kathleen A. M.; Hollinger, Maile K.; Velez, Tania E.; Leone, Vanessa A.; Chang, Eugene B.; Sperling, Anne I. (Respiratory research, 2022)
Airway instillation of bleomycin (BLM) in mice is a widely used, yet challenging, model for acute lung injury (ALI) with high variability in treatment scheme and animal outcomes among investigators. Whether the gut microbiota plays any role in the outcome of BLM-induced lung injury is currently unknown. Intratracheal instillation of BLM into C57BL/6 mice was performed. Fecal microbiomes were analyzed by 16s rRNA amplicon and metagenomic sequencing. Germ-free mice conventionalization and fecal microbiota transfer between SPF mice were performed to determine dominant commensal species that are associated with more severe BLM response. Further, lungs and gut draining lymph nodes of the mice were analyzed by flow cytometry to define immunophenotypes associated with the BLM-sensitive microbiome. Mice from two SPF barrier facilities at the University of Chicago exhibited significantly different mortality and weight loss during BLM-induced lung injury. Conventionalizing germ-free mice with SPF microbiota from two different housing facilities recapitulated the respective donors' response to BLM. Fecal microbiota transfer from the facility where the mice had worse mortality into the mice in the facility with more survival rendered recipient mice more susceptible to BLM-induced weight loss in a dominant negative manner. BLM-sensitive phenotype was associated with the presence of Helicobacter and Desulfovibrio in the gut, decreased Th17-neutrophil axis during steady state, and augmented lung neutrophil accumulation during the acute phase of the injury response. The composition of gut microbiota has significant impact on BLM-induced wasting and death suggesting a role of the lung-gut axis in lung injury.